VALUATION OF BUMN CONSTRUCTION COMPANY STOCK PRICES AT THE TIME OF A BULLISH AT THE INDONESIAN STOCK EXCHANGE - Utamaningsih, Arni (Jurnal Aplikasi Manajemen, 2020)
This study provides an assessment of the stock prices of BUMN construction companies when the stock market in Indonesia is bullish. This study uses historical data for 2015-2018 to project stock prices in the next five years. The method used is the application of WACC, Cost of Equity, to terminate the value and value of the firm. The results showed that the company has high debt and sales costs, resulting in a decreased capital structure. The decline in capital structure performance affects investor valuations as reflected in the rise in stock prices. We are considering improving the capital structure. Future studies can develop micro aspects of valuing stock prices.